#TITLE_ALTERNATIVE# - GUNAWAN SUPRIATNA (NIM13203097); Pembimbing: Dr.Ir. Pekik Argo Dahono, ERIK
In this final project, analysis and minimization of ripple in the AC and DC side of five phase PWM inverter is presented under sinusoidal and non-sinusoidal load emf. Analysis begins with deriving the rms value of AC side current ripple in PWM inverter as a function of reference signal. Under sinusoidal load emf, it is shown that optimum reference signal that result in minimum ripple output current is sinusoidal reference signal. Under non-sinusoidal load emf, it is found that fifth harmonic is the optimum injection signal that can be used to reduce the output ripple current five phase inverter. Fifth harmonic can also increase the maximum modulation index. Output current ripple under non-sinusoidal load emf is lower compared with total output ripple produced under sinusoidal load emf. In the analysis of ripple in the DC side five phase PWM inverter, it is shown that the rms value of input current ripple is not influenced by the shape of the reference signal and switching frequency. Optimum reference modulating signal that produces a minimum total ripple in the dc side voltage under sinusoidal load emf is pure sinusoidal modulating signal. Simulation result is also presented to show the validity of derived expression.